THe EFFECT OF DHIKR JAHR THERAPY AS AN INTERVENTION TO REDUCE ANXIETY IN THE ELDERLY WITH HYPERTENSION - Rahayu, Arinda Tri; Ts. Fitriyah, Erna; Camelia, Dina; Wahdi, Achmad; Fatma Pratiwi, Tiara (STIKES Insan Cendekia Medika Jombang, 2024)
Introduction: Hypertension is referred to as